Emotion regulation in disordered eating: Psychometric properties of the Difficulties in Emotion Regulation Scale among Spanish adults and its interrelations with personality and clinical severity - Wolz, Ines; Agüera, Zaida; Granero, Roser; Jiménez-Murcia, Susana; Gratz, Kim; Menchon, Jose M.; Fernandez-Aranda, Fernando (Frontiers in Psychology, 2015)
Objective: The aims of the study were to 1) validate the Difficulties in Emotion Regulation Scale (DERS) in a sample of Spanish adults with and without eating disorders, and 2) explore the role of emotion regulation difficulties in eating disorders, including its mediating role in the relation between key personality traits and ED severity Methods: 134 patients (121 female, mean age = 29 years) with anorexia nervosa (n = 30), bulimia nervosa (n = 54), binge eating (n = 20), or Other Specified Feeding or Eating Disorders (n = 30) and 74 healthy control participants (51 female, mean age = 21 years) reported on general psychopathology, eating disorder severity, personality traits and difficulties in emotion regulation. Exploratory and confirmatory factor analyses were conducted to examine the psychometrics of the DERS in this Spanish sample (Aim 1). Additionally, to examine the role of emotion regulation difficulties in eating disorders (Aim 2), differences in emotion regulation difficulties across eating disorder subgroups were examined and structural equation modeling was used to explore the interrelations among emotion regulation, personality traits, and eating disorder severity. Results: Results support the validity and reliability of the DERS within this Spanish adult sample and suggest that this measure has a similar factor structure in this sample as in the original sample. Moreover, emotion regulation difficulties were found to differ as a function of eating disorder subtype and to mediate the relation between two specific personality traits (i.e., high harm avoidance and low self-directedness) and eating disorder severity. Conclusions: Personality traits of high harm avoidance and low self-directedness may increase vulnerability to eating disorder pathology indirectly, through emotion regulation difficulties.